Physical birth outcomes in neonates prenatally exposed to buprenorphine – our first experiences - Natasha Simonovska; Beti Zafirova-Ivanovska; Aleksandra Babulovska (My University, 2019)
Introduction/Objective Buprenorphine appears generally similar to, and in some cases superior to, methadone in terms of maternal, fetal, and neonatal outcomes. The objective of the study was to assess some physical birth outcomes in neonates prenatally exposed to buprenorphine. Methods During a seven-year period, nine patients have been treated with buprenorphine during their pregnancy. All women underwent interview, clinical investigations, biochemical analysis, toxicological screening, viral markers for hepatitis B, C, HIV, with regular check-ups by an obstetrician and a psychiatrist. Newborn outcomes included: birth weight in grams, birth length in centimeters, physical anomalies, head/chest circumference in centimeters, Apgar score at 1 minute / 5 minutes, gestational age (weeks), newborn length of hospital stay in days, breast-feeding, the newborn’s need for pharmacologic treatment after delivery. Results The mean birth weight was 2,991.11 ± 37 g; birth length was 49.44 ± 2.29 cm; head circumference was 33.11 ± 0.78 cm; chest circumference was 32.33 ± 1 cm; first minute Apgar score was 8.22, fifth minute 9.22; age at delivery was 38.77 ± 1.09 weeks; hospitalization after delivery 4.44 ± 1.13 days. None of the newborns had physical anomalies. Six of the newborns were breastfed. Conclusion Buprenorphine is a safe and important part of a complete comprehensive treatment approach in pregnant women with opioid use disorder. Buprenorphine treatment of maternal opioid use disorder indicated a low risk of preterm birth, normal birth weight and length, head and chest circumference, Apgar score, short hospitalization after delivery.
Keywords: buprenorphine; pregnancy; neonates; physical birth outcomes